Kirkebyggeri i Hammerum herred - Vingborg, Jørgen (Kirkehistoriske Samlinger, 1992)
In the Hammerum district on the Jutland Heath several churches will soon celebrate their first 100 years. The background for the building of these churches - which have many traits in common - is to be found in the development of the local commmunities and in the religious revival movements. The district and its immediate surroundings had been characterized by large distances and bad communications, scarcity of population, poverty, and unsatisfactory schooling facilities. But in the course of the 19th century great progress was made in all respects. So, in consequence of the people being awakened religiously and culturally, they wanted to have more churches built. As they could not afford to do it all by themselves, they applied to Parliament which then appointed a commission to examine the facts and come up with proposals for a co-ordinated effort. After having deliberated in 1882-83, the commission proposed to erect 16 new churches and 8 rectories for the sum total of 310.500 kroner. Then, for a number of years, nothing happened. This was partly due to parliamentary conditions being difficult during the time of the Provisional Laws, and partly to the fact that the estimated price proved unrealistic. Also, as time went by, new applications came in. In 1889, however, Herning church was built as the first, and two years later, more constructions got under way, resulting in well over 20 buildings in all. The majority of the churches were designed by three architects: C. A. Wiinholt, H. V. Ahlmann, and R. Frimodt Clausen. In the article, a closer look is taken at Wiinholt’s churches, and a connection is established between them and Viborg Cathedral and its architect H.B. Storck as well as its decorator, the renowned wallpainter Joakim Skovgaard. The article presents mainly suggestions, but the forthcoming jubilees should provide a fine occasion for the closer study that these buildings - often condescendingly called smallholderchurches - amply merit.